Pengaruh Audit Fee, Opini Audit, dan Audit Delay terhadap Auditor Switching dengan Financial Distress sebagai Variabel Moderasi - Susana Milo; Maulana Malik Muhammad (UNIVERSITAS KALBIS, 2022)
This study aims to determine the effect of audit fees, audit opinion and audit delay on auditor switching with financial distress as a moderating variable. The population in this research are linfrastructure, utility and transportation sector companies listed on the Indonesia Stock Exchange (IDX) in 2015-2019. The number of research samples obtained is 40 companies with using purposive sampling method and the amount of research data obtained is 200. The data analysis method used is regression logistic analysis.. The results of the study indicate that the audit fee have no effect on auditor switching, audit opinion has a significant negative effect on auditor switching and audit delay have no effect on auditor switching and the financial distress variable is not able to moderate the effect of audit fee, audit opinion and audit delay on auditor switching